PKM: Kewirausahaan Digital Untuk Karang Taruna Desa Kedawung - Fatihanursari Dikananda; Irfan Ali; Nizar Fazari Hidayat; Rheznandya Fahreza (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The The rapid development of digital technology has opened new opportunities in the entrepreneurial field, especially among the youth. This study, titled “Digital Entrepreneurship for the Karang Taruna of Desa Kedawung,” is designed to identify existing digital potentials and to develop an innovative digital entrepreneurship model aimed at empowering Karang Taruna members by generating job opportunities and enhancing the welfare of the local community. The study employs a mixed-method approach by integrating both qualitative and quantitative methods to analyze the barriers, potentials, and optimal strategies in harnessing digital technology as an economic empowerment tool. The research methodology includes field surveys, in-depth interviews with business practitioners and community leaders, and a comprehensive literature review from various relevant sources. The findings indicate that the digital divide and insufficient training are the primary obstacles to effective digital entrepreneurship implementation. In response, an intensive mentoring program combined with digital literacy training emerges as an effective solution to overcome these challenges. This program not only improves technical skills related to digital platforms but also enhances managerial competencies and entrepreneurial creativity. Furthermore, strategic partnerships with industry players and local academics are expected to foster a sustainable business ecosystem. The implications of this research are significant, as it provides a replicable model for digital entrepreneurship development that can be adapted to similar rural contexts. Active involvement from both governmental and private sectors is crucial to support the program’s sustainability through funding, infrastructure development, and market access. Consequently, this study contributes not only to local economic development but also to reducing youth unemployment, raising community welfare, and accelerating digital transformation in rural areas.